Theoretical and numerical investigation of bridge frequency identification employing an instrumented vehicle in stationary and moving states. (May 2023) - Hashlamon, Ibrahim; Nikbakht, Ehsan
Abstract: In this study, theoretical and numerical means are used to investigate frequency identification of bridges using a vehicle in moving and stationary states. Unlike previous experimental studies, the current investigations provide theoretical and numerical understating of the stationary vehicle response due to the movement of another vehicle. First, the study introduces a novel closed-from solution of the dynamic responses of a vehicle in stationary state while the bridge is excited by another moving vehicle. The proposed equations are validated using a finite element (FE) model. Then, vehicle-to-bridge amplitude ratio is used to determine visibility of bridge frequency in the responses obtained by the closed-form solutions of moving and stationary vehicles. For an undamped and smooth surface conditions (assumptions used for the closed-from solution), the moving vehicle provided higher visibility of bridge frequency than that of the stationary vehicle parked at mid-span. To investigate the effects of damping and road roughness, numerical FE simulation is conducted. When the speed of the moving truck-trailer is 8 m/s and road roughness profile is of class A, 2nd and 3rd modes of bridge frequencies were not visible in the response of the moving vehicle, however; the stationary vehicle could detect all modes of frequencies up to the 3rd mode. For the first mode, although it was detected successfully by both moving and stationary vehicles, higher visibility of the stationary vehicle specially at quarter-span was always noticed. When lower speed of 2 m/s was used for the moving vehicle, 2nd and 3rd modes were identified successfully by both the moving and stationary vehicles, but with higher visibility in the stationary vehicle. However, when road roughness of class B was used, the moving vehicle again could not detect the 2nd and 3rd modes unlike the stationary vehicle.